Politeness Principle Obedience on Governor and Vice Governorâ€™s Utterances in the â€œKandidat Bicara Talk Showâ€ (Universitas Negeri Semarang, 2019)
Speech politeness should be done by all elements of society, especially candidate of governor and vice-governor. Politeness principle is indicated by obedience of politeness principle maxims. This research aims to analyze politeness principle obedience of candidate of governor and vice-governor speech in candidate talk show. This pragmatic descriptive research collected data by observation. It consisted of basic and advance observation techniques. This technique used recording technique. The extended techniques were participant observer, recording, and noting. The data was analyzed by pragmatic equivalent and normative method. Based on the research, the obedience of politeness principle maxims consisted of (1) Tact Maxim, (2) maxim of generosity, (3) maxim of approbation, (4) maxim of humility, (5) maxim of agreement, and (6) maxim of sympathy. This research is expected to contribute in developing linguistics study and enriching knowledge dealing with politeness principle obedience for governor and vice â€“ governor candidates.